CAP and Cloud Data Management. - Ramakrishnan, Raghu (Computer (00189162), 2012)
Novel systems that scale out on demand, relying on replicated data and massively distributed architectures with clusters of thousands of machines, particularly those designed for real-time data serving and update workloads, amply illustrate the realities of the CAP theorem. The featured Web extra is a video interview with Yahoo's Raghu Ramakrishnan about CAP and the cloud.